Keterampilan Proses Sains Siswa Jurusan IPA Beberapa SMA Di Yogyakarta - Hutomo Eri Pratama; Supardi Supardi (PANDITA : Interdisciplinary Journal of Public Affairs, 2023)
This research is quantitative research that aims to determine the extent of mastery of science process skills of grade XI students of the Science Department in four high schools in Yogyakarta and find out the differences in mastery of science process skills of grade XI students of the Science Department in four high schools in Yogyakarta. The subjects of this study were 127 grade IX students majoring in science in several high schools in Yogyakarta. The results showed that the mastery level of students majoring in science at four high schools in Yogyakarta was still at a sufficient level. There are significant differences in the level of mastery of science process skills from science majors from the four schools used as research sites. Mastery of science process skills of science students majoring in the aspect of identifying variables still needs improvement while mastery of science process skills in defining variables operationally, and designing research / experiments is still at a sufficient level. The ability to present/interpret data and formulate hypotheses is a skill that students master well.Keywords: Science Process Skills, Science Major Students